The Role of Knowledge Management in Enhancing Innovation in R&D Industry: A Literature and Empirical Review - Mardiah, Mardiah; Khalidy, Furqan; Budiman, Arief (Raskha Media Group, 2025)
Innovation is a key driver of competitiveness and sustainability in the Research and Development (R&D) industry. As knowledge-intensive organizations, R&D institutions rely heavily on the effective management of knowledge to accelerate discovery, streamline processes, and create value. This study aims to examine the role of Knowledge Management (KM) in enhancing innovation within the R&D sector by reviewing relevant literature and analyzing empirical findings from selected case studies. The review highlights that KM practices such as knowledge sharing, codification, retention, and collaboration are closely linked to higher innovation performance. Empirical evidence shows that organizations that invest in structured KM frameworks tend to exhibit greater adaptability, faster product development cycles, and improved cross-functional synergy. However, challenges such as cultural resistance, lack of incentives, and inadequate technological support still hinder optimal KM implementation. The findings suggest that integrating KM into the core innovation strategy, supported by leadership commitment and digital infrastructure, can significantly boost innovation capacity in R&D environments. This study contributes to the growing discourse on KM by offering insights into its practical and strategic relevance for innovation management in knowledge-driven industries.